A new art : photography and impressionism - Westheider, Ortrud; Philipp, Michael, 1962-; Zamani, Daniel; Pohlmann, Ulrich (Prestel, 2022)
"In the 19th century, numerous photographers chose the same motifs as Impressionist painters: the forest of Fontainebleau, the cliffs of Étretat or the modern metropolis of Paris. They, too, studied the changing light, seasons and weather conditions. From its inception, photographers pursued artistic ambitions, as evidenced by their experimentation with composition and perspective, by means of various technical procedures. Until the First World War, the relationship between photography and painting was characterized both by competition and mutual influence. The exhibition and catalogue examine these interactions and illuminate the development of the new medium from the 1850s to its establishment as an autonomous art form around 1900"--